2020
DOI: 10.48550/arxiv.2007.02442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GRAF: Generative Radiance Fields for 3D-Aware Image Synthesis

Katja Schwarz,
Yiyi Liao,
Michael Niemeyer
et al.

Abstract: While 2D generative adversarial networks have enabled high-resolution image synthesis, they largely lack an understanding of the 3D world and the image formation process. Thus, they do not provide precise control over camera viewpoint or object pose. To address this problem, several recent approaches leverage intermediate voxel-based representations in combination with differentiable rendering. However, existing methods either produce low image resolution or fall short in disentangling camera and scene propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 40 publications
0
84
0
Order By: Relevance
“…They have been extended to achieve dynamic scene capture [27,39], relighting [3,5], appearance editing [57], fast rendering [16,61], and generative models [7,36,45]. However, most methods [3,27,39,57] still follow the original NeRF framework and train per-scene MLPs to represent radiance fields.…”
Section: Related Workmentioning
confidence: 99%
“…They have been extended to achieve dynamic scene capture [27,39], relighting [3,5], appearance editing [57], fast rendering [16,61], and generative models [7,36,45]. However, most methods [3,27,39,57] still follow the original NeRF framework and train per-scene MLPs to represent radiance fields.…”
Section: Related Workmentioning
confidence: 99%
“…Appearance mapping network where ξ is the camera pose for calculating the 3D coordinate x and the viewing direction d (Schwarz et al 2020). Below, we describe the model structure designed for CG-NeRF in detail.…”
Section: Proposed Approach Overviewmentioning
confidence: 99%
“…While these techniques utilize NeRF only for synthesizing an unseen view, recent studies have emerged that generate photorealistic multi-view images based on generative adversarial networks(GANs) (Schwarz et al 2020;Niemeyer and Geiger 2021c;Chan et al 2021). Compared to the existing 2D-based generative models, these studies can produce 3D-aware images by generating view-consistent images for given camera poses.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the fully differentiable learning process allows the MLP to learn complex signals from sparsely available data points to reconstruct high-quality images or objects. Recent research has demonstrated the effectiveness of coordMLPs for a wide range of signal fitting or learning tasks such as image super-resolution (Chen et al, 2021), 3D shape representation (Park et al, 2019;Mescheder et al, 2019;Gropp et al, 2020), novel view synthesis Schwarz et al, 2020) and photo-realistic 3D scene editing (Niemeyer & Geiger, 2021). The search for more accurate and generalizable implicit neural network architectures and methodologies is an active area of research.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, proposes a positional encoding (PE) method that maps the original input coordinates into a high dimensional space using a series of high frequency functions to better capture high frequency variations. A common way to enrich the representation power of these models is to add latent codes/features as additional inputs to the coordMLPs (Schwarz et al, 2020;Park et al, 2021;Chen et al, 2021;Mehta et al, 2021). These additional inputs are combined with positional coordinates and are essentially treated as additional dimensions in the input coordinates.…”
Section: Introductionmentioning
confidence: 99%